2015
DOI: 10.1681/asn.2013101033
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Gene Deficiency Causes Salt-Sensitive Hypertension via Monocyte Chemotactic Protein-1/CC Chemokine Receptor 2–Mediated Inflammation

Abstract: Klotho (KL) is a newly discovered aging suppressor gene. In mice, the KL gene extends the lifespan when overexpressed and shortens the lifespan when disrupted. This study investigated if KL deficiency affects BP and salt sensitivity using KL mutant heterozygous (+/2) mice and wild-type (WT) mice (9 weeks of age, 16 mice per group). Notably, systolic BP in KL(+/2) mice began to increase at the age of 15 weeks, reached a peak level at the age of 17 weeks, and remained elevated thereafter, whereas systolic BP rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 57 publications
6
85
0
1
Order By: Relevance
“…38,39 Our recent study showed that high salt-induced kidney damage in KL(+/2) mice may involve activation of the MCP-1/CCR2 pathway and infiltration of T cells and macrophages. 16 Although we cannot exclude the contribution of hypertension to renal impairment in KL(+/2) mice, consistent results of other studies without the confounding interference of hypertension 7,40,41 suggest that the activated inflammatory process could play an independent and important role in renal damage.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…38,39 Our recent study showed that high salt-induced kidney damage in KL(+/2) mice may involve activation of the MCP-1/CCR2 pathway and infiltration of T cells and macrophages. 16 Although we cannot exclude the contribution of hypertension to renal impairment in KL(+/2) mice, consistent results of other studies without the confounding interference of hypertension 7,40,41 suggest that the activated inflammatory process could play an independent and important role in renal damage.…”
Section: Discussionsupporting
confidence: 61%
“…16 This study further shows that upregulation of aldosterone levels is responsible for the inflammation seen in KL(+/2) mice, because blockade of aldosterone receptors abolishes leukocyte infiltration and cytokine releases in kidneys (Supplemental Figures 4 and 5). Although FGF23 was reported to increase the membrane abundance of NCC, tubular uptake of sodium, and BP in WT mice, high serum levels of FGF23 1,26 failed to increase Na reabsorption and BP in KL(2/2) mice.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Notably, a recent study has implicated Klotho deficiency in causing salt-sensitive hypertension in mice, 20 supporting the role of Klotho in regulating blood pressure. In view of the fact that RAS activation, not only plays a role in the evolution and progression of CKD, but also is a causative factor for developing hypertension and cardiovascular diseases, 7,45 our studies on the intimate connection between loss of Klotho and RAS activation would have wide implications beyond CKD.…”
Section: Klotho Inhibits Rasmentioning
confidence: 82%
“…Immunohistochemical (IHC) procedures were performed as described in our previous studies (Crosswhite et al ., 2014; Chen et al ., 2015; Lin & Sun, 2015a,c; Zhou et al ., 2015b). Western blotting was performed as described in our previous studies (Goetz et al ., 2010; Belting et al ., 2012; Chen et al ., 2015; Lin & Sun, 2015b,c; Zhou et al ., 2015a; Lin et al ., 2016). For details, see the Appendix S1 (Supporting information).…”
Section: Methodsmentioning
confidence: 99%